Antimicrobials in Livestock Farming and Resistance: Public Health Implications - Marilena Trinchera; Silvia De Gaetano; Elenoire Sole; Angelina Midiri; Serena Silvestro; Giuseppe Mancuso; Teresa Catalano; Carmelo Biondo (Antibiotics)
The accelerated spread of bacterial resistance has been demonstrated to reduce the effectiveness of antibiotic treatments for infections, resulting in higher morbidity and mortality rates, as well as increased costs for livestock producers. It is expected that the majority of future antimicrobial use will be in animal production. The management of antimicrobial resistance (AMR) in the livestock sector poses significant challenges due to the multifaceted nature of the problem. In order to identify appropriate solutions to the rise of antimicrobial resistance, it is imperative that we have a comprehensive understanding of the disease dynamics underpinning the ways in which antimicrobial resistance is transmitted between humans and animals. Furthermore, in consideration of the anticipated requirement to satisfy the global demand for food, it is imperative that we guarantee that resistance is not transmitted or propagated during the treatment and disposal of animal waste, particularly from intensive farming. It is also crucial to formulate a research agenda to investigate how antibiotic resistance in animal faeces from livestock farming is affected by intensified farming activities. The review analyses the environment’s role in the transmission resistance chain and reviews methodologies for disrupting the link. A particular focus is placed on the limitations of the applied methodologies to reduce antimicrobial resistance in global animal production.